Demokrasi di Indonesia : demokrasi parlementer dan demokrasi pancasila - Budiardjo, Miriam (Jakarta : PT Gramedia Pustaka Utama, 1994)
Democracy in Indonesia ; collected papers
Keywords: Democracy -- Indonesia; Pancasila; Indonesia -- Politics and government -- 20th century